Investigating the role of amine in InP nanocrystal synthesis: destabilizing cluster intermediates by Z-type ligand displacement. Issue 1 (1st December 2016) - Gary, Dylan C.; Petrone, Alessio; Li, Xiaosong; Cossairt, Brandi M.
Abstract : The reaction of primary amines with carboxylate-capped InP clusters is found to remove indium carboxylate subunits from the cluster surface, resulting in a structural rearrangement to alleviate core strain and passivate phosphorus atoms. Abstract : The reaction of primary amines with In37 P20 (O2 CR)51 is found to remove In(O2 CR)3 subunits from In37 P20 (O2 CR)51 . This loss of Z-type ligands coincides with structural rearrangement to alleviate core strain and passivate phosphorus atoms. This result consolidates conflicting claims that primary amines both promote and retard precursor conversion rates for InP nanocrystals.